Construction of Dual‐Mesoporous Carbon Fibers Via Coassembly for Supercapacitors. Issue 23 (4th November 2020) - Du, Juan; Lv, Haijun; Yu, Yifeng; Chen, Aibing
Abstract : Mesoporous carbon fiber (MCF) has shown great application prospects in the field of electrochemical energy storage due to its large specific surface area, large draw ratio, fast electron transfer ability, and good cycle stability. Herein, the dual‐mesoporous carbon fibers (DMCF) is prepared via a coassembly process with phenolic resin oligomers as carbon precursors, sodium silicate (silica precursor) as an assistant, and cetyltrimethylammonium bromide and pluronic F127 as templates. The silica and F127 micelles provide mesoporous sizes of 3.8 and 2.6 nm, respectively. The obtained DMCF has fibrous morphology, high specific surface area, and double mesoporous structure. Compared with carbon fibers with a single pore distribution, DMCF exhibits an excellent specific capacitance of 264 F g −1 at 0.5 A g −1 and shows good cycle stability as an electrode material in supercapacitors, demonstrating the enormous potential of DMCF in energy‐storage applications. Abstract : A nitrogen‐doped porous carbon with enhancement in the rate capability and electrochemical performance in supercapacitors is prepared by simple solid‐phase grinding using silica sphere as the hard template, FeCl3 ·6H2 O as the oxidant, aniline as the carbon and nitrogen precursor.